Changing Livelihood Strategies of the Tharu Community in Tilpur, Surkhet: Drivers, Trends, and Impacts - Sharma, Mahesh; Khadka, Ghanshyam; Adhikari, Deepak (Karnali Outlook: Knowledge Across Disciplines, 2026)
This research focuses on Tilpur, the Tharu community in Nepal’s Surkhet District, in Birendranagar Municipality. The Tharu are one of Nepal’s Indigenous groups. Ethnographically, subsistence farming had been the primary and only occupation, diversified only since other socio-economic, infrastructural, and cultural changes have occurred. This research used a mixed-methods approach, including a household survey, interviews, and participant observation, with a sample of 44 Tharu households to capture changes and their effects on the community’s structure from demographic, economic, and cultural perspectives. The predominant occupation in the community is agriculture, and is practised by 72% of the community. However, the community is shifting towards agricultural practices and diversifying into other business activities and foreign employment. Farming practices have changed due to factors such as land fragmentation and use, as well as urbanisation, leading to greater adoption of modern agriculture. Educational attainment in the community remains moderate, and a very small proportion of the population pursues studies beyond the School Leaving Certificate. The community is influenced by modernisation, and marriage trends, cultural patterns, dress, and celebrations are shifting towards those of neighbouring societies. Fuel energy consumption trends also reflect a shift from conventional fuels to biogas and LPG. Although there are positive changes in income and awareness, issues regarding smallholder land, poor agricultural inputs, and cultural protective risks still remain. The research underscores the need for integrating comprehensive policies that economically benefit and protect the Tharu community’s cultural traits. The results document indigenous populations’ livelihood practices and community responses to rapid changes in Nepal’s rural economy.